2020
DOI: 10.1002/acm2.13056
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the preconfigured Varian Ethos Acuros XB Beam Model for treatment planning dose calculations: A dosimetric study

Abstract: Varian (Palo Alto, California, United States) recently released an online adaptation treatment platform, Ethos, which has introduced a new Dose Preview and Automated Plan Generation module despite sharing identical beam data with the existing Halcyon linac. The module incorporates a preconfigured beam model and the Acuros XB algorithm (Ethos AXB model) to generate final dose calculations from an initial fluence optimization. In this study, we comprehensively validated the accuracy of the Ethos AXB model by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) radiotherapy for esophageal cancer patients at dedicated X-ray based systems [25,26]. Previous studies on radiation-induced toxicity after chemoradiation for esophageal cancer showed multiple correlations between an increase in lung and heart dose and pulmonary and cardiac complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) radiotherapy for esophageal cancer patients at dedicated X-ray based systems [25,26]. Previous studies on radiation-induced toxicity after chemoradiation for esophageal cancer showed multiple correlations between an increase in lung and heart dose and pulmonary and cardiac complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple online adaptive treatment platforms have been released by various vendors which allow for online replanning and thereby potentially by-passing all interfractional anatomy geometry variations. These platforms could either be based on X-ray imaging [25,26] or MR imaging [27][28][29] and could have onboard imaging capabilities that allow for online intrafraction monitioring to allow gating [30,31] and tracking [32] to mitigate effects from intrafraction motion.…”
mentioning
confidence: 99%
“…The Halcyon is delivered with the Eclipse treatment planning system (TPS) from the same manufacturer (Varian Medical Systems), which includes a fully preconfigured photon beam model based on the reference beam data. Extensive validation tests have been performed and installed systems have been found to accurately match the reference beam data preconfigured in Eclipse, including percentage depth doses, profiles, and output factors 3,5 . It has also been reported that the system complies with commissioning criteria from international guidelines 6–11 and a good agreement between measurements and calculations for clinical plans was found in patient‐specific quality assurance (QA) tests, end‐to‐end verifications and external audits 2,3,12 …”
Section: Introductionmentioning
confidence: 91%
“…Extensive validation tests have been performed and installed systems have been found to accurately match the reference beam data preconfigured in Eclipse, including percentage depth doses, profiles, and output factors. 3,5 It has also been reported that the system complies with commissioning criteria from international guidelines [6][7][8][9][10][11] and a good agreement between measurements and calculations for clinical plans was found in patient-specific quality assurance (QA) tests, end-to-end verifications and external audits. 2,3,12 RayStation (RaySearch Laboratories, Stockholm, Sweden), a TPS independent of treatment units' manufacturers, is also commercially available for the Halcyon.…”
Section: Introductionmentioning
confidence: 95%
“…[18][19][20] The dosimetric accuracy of the Ethos treatment planning system has previously been comprehensively verified. 21 The workflow used on Ethos for online adaptive prostate patients involves the use of "influencer" structures that are initially auto-contoured using AI. The influencer structures are then adjusted by the user if necessary and used to create a structure-guided deformable image registration (DIR) between the planning computed tomography (CT) scan and the acquired cone beam computed tomography (CBCT) scan.…”
Section: Introductionmentioning
confidence: 99%